The Paradox of CBC Implementation: Why Does Teacher Training Fail to Translate to Mastery of Curriculum Assessment and Learning Improvement in Public Elementary Schools? - Mwereria Miriti Joseph; Ruth Thinguri; Jane Muigai (Nurul Jadid University, 2025)
This study examines the complexity of implementing the Competency-Based Curriculum (CBC) in public primary schools in Igembe Central Sub-district, Kenya, a crucial education reform aimed at shaping 21st-century skills. Although CBC implementation efforts have been made, challenges such as inadequate syllabus coverage, ineffective teaching methods, and suboptimal learner learning outcomes remain a serious concern. This study aims to investigate the influence of teacher training on the implementation of CBC in these schools. Adopting a mixed methods approach with a concurrent triangulation research design, the study collected data from 394 participants through questionnaires, interviews, observations, and document analysis. Quantitative data were analyzed using descriptive and inferential statistics (SPSS Version 25), while qualitative data were analyzed thematically. The study's results revealed that the implementation of CBC remains a primary concern in the Igembe Central Sub-district public elementary school. A significant proportion of teachers do not complete the syllabus, resulting in substandard student learning outcomes in critical areas. This is mainly due to the lack of adequate teacher training related to curriculum-based assessments. The findings of this study imply the importance for the Ministry of Education (MoE) to sustainably pursue teacher training and retraining programs to address identified competency gaps, in order to enhance the effectiveness of CBC implementation.